PENGEMBANGAN MEDIA FLIPBOOK PADA PEMBELAJARAN BAHASA INDONESIA MATERI FABEL PADA SISWA KELAS IV SEKOLAH DASAR - Nurul Istiq'faroh; Aimatul Aliyah (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2022)
The background in the wwriting of this study is that less effective learning takes place in those schools and less teching media. Researchers also perfom a tet based analysis of the student book that outlines only tet at the fable story study. the reseach objective are (1) to product learning media flipbook theme 4 in subtheme 1 in the first learning process in Indonesian language subject. The fabel is a form of narration, or fairy tales whose characters use animals that talk and behave like humans. (2)to find the advisability of learning media flipbook by validity out come of advisability validator. In this reseach used developer research with 4D model wich developer by Thiagarajan. The model adapted by 3 steps. The media wich developed in this research validated by 3 validator the result of research in this advisability flipbook media: Validator 1 from media expert get the result based on 88% in category golden, validator 2 from a material expert get the result 92% in category golden, validator 3 from linguists get the result 80% in category good. Based on the result before media wich developed in this research declared appropriate to use in the learning process.